The Use of Generative Learning Model in Improving Students’ Understanding of Mathematical Concepts of Al-Azhar 19 Islamic High School - Kosiret, Andri; Indiyah, Fariani Hermin; Wijayanti, Dwi Antari (International Journal of Progressive Mathematics Education, 2021)
Background. Distance learning during the COVID-19 pandemic has changed the landscape of mathematics learning as a whole. One of the mathematics learning models that offer new concepts in distance learning is generative learning model. The Aim of the Research. This study will evaluate the effectiveness of the implementation of generative learning models in improving students' mathematical understanding abilities. The appropriate research method to test the effectiveness is quasi-experimental design because the class being experimented with is not changed, so that it does not have much effect on overall learning stability. The research sample used cluster random sampling technique where class X MIPA 3 was the experimental class while class X MIPA 2 was the control class. The research instrument used was a test of students' ability to understand mathematical concepts in the material of Logarithmic Equations as many as seven essay questions. Conclusion. There is an effect (high) of the generative learning model on the ability to understand students' mathematical concepts applied to the distance learning system at Al-Azhar 19 Ciracas Islamic Senior High School logarithmic equation material with a significance level of α = 0.05. Contribution. This study offers a new concept for the application of distance learning mathematics by implementing a generative learning model which in this study has contributed positively to student understanding